No correlation between lunar and menstrual cycle: an early report by the french physician J.A. Murat in 1806 - Lemmer, Björn (Chronobiology international, 2019)
Jean Arnaud Murat was a physician at the Medical School of Montpellier in France. In 1806 he published his outstanding book “De L’Influence de la Nuit sur les Maladies ou Traité des Maladies Nocturne”. In his book he concentrated on the following questions:- Does the night has an influence on a disease?- Are there diseases in which this is more or less obvious?- What is the physical background of this influence?Murat described in detail certain diseases which dominate at night and he concluded that the most evident motivation for his observations is the constant and periodic movement of the earth around its axis, resulting in a period of about 24 h, and the elliptic rotation around the sun. Most important Murat presented for the first time data that the menstrual cycle is not governed by the lunar cycle.